(3QSGdI aj GdQO Ydi GdWGFaI GdJLGfjIs - (3Ydj Hf eMeO Gdejdj GdLeGdj GdeZQHj GdeGdcj,J (B1248 (3g` s ((3YeQ Hf ecMeO YHO GdeLjO GdYQGbi GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg GdeNJU HGdCRdjI s
(3BNQgG (B:s
(3HJMdjd LejY UaGJi Mi dG Jchf GfJgi s
(3Vef eLehY s
(3jJdh QSGdI ai GdJUhas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B17 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B235s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs